Insights into CO2 conversion in pulsed microwave plasma using optical spectroscopy. Issue 41 (October 2020) - Britun, N.; Godfroid, T.; Snyders, R.
Abstract: Low pressure surfaguide microwave discharge working in pulsed regime and used for CO2 conversion is characterized by optical spectroscopy methods aiming at better understanding of the conversion process. The rotational, vibrational, and electron excitation in plasma were studied. The translational (T gas ) and vibrational (T vibr ) temperatures are found elevated in the discharge active zone. At low pressure ( < 1 Torr) discharge demonstrates non-equilibrium with T gas ∼ 700 K (0.06 eV) and electron temperature (T e ) of nearly 2 eV. Non-equilibrium state gradually disappears as the gas pressure increases, resulting in a growth of T gas and decrease of T e . T vibr of nitrogen also slowly decreases towards the equilibrium condition. The CO2 conversion and energy efficiencies have been examined as a function of the discharge pulse parameters, such as the plasma pulse duration, repetition rate and duty ratio, clarifying additional possibilities for optimization of conversion in the pulsed microwave discharges.